Examining the economic viability of clove farming and its impact on the welfare of farmers in Larompong Sub-District - Andi Ismi Yanti; Adzan Noor Bakri (IAIN Palopo, 2023)
Abstract: This thesis discusses the profitability of clove farming and the welfare of clove farmers in Larompong District. This thesis is of a quantitative type; the location of this research is Larompong District from June to July, for the population and sample, namely the clove farming community in Larompong District and with a sample of 30 people. The data sources for this research were primary and secondary data, while the data collection methods were direct observation and population and sample collection by random sampling or random sampling. The results of this study indicate that with a total acceptance of Rp. 44,400,000 is then reduced by the total cost of IDR 1,218,183 so the total income received is IDR 43,181,817. so the NPM of clove farming in the Larompong sub-district is 97% which is relatively high and able to provide benefits, while determining the level of welfare using NTP (Farmers Exchange Rate) analysis by looking at the average household expenditure of Rp.9,583,334 and farming income cloves of Rp.44,400,000 so that it can be seen that the NTP of this clove farming is 436%, which when NTP> 100 means that it indicates a surplus or an increase in welfare